Substance P Antagonism Prevents Chemotherapy-Induced Cardiotoxicity - Legi, Ashiq (Cancers (Basel), 2021)
SIMPLE SUMMARY: Anthracyclines are a class of chemotherapeutics that are an essential component of many treatment regimens for solid and blood tumors. Doxorubicin (DOX), an anthracycline is broadly considered the most active single agent available for many cancers. However, effective use of anthracyclines is limited due to the possibility of cardiotoxicity, thus causing restrictions on treatment options for treatable cancers. Our studies indicate the SP/NK1R system as a promising novel target and use of NK1R antagonists as a translational tool for prevention of chemotherapy-associated cardiotoxicity in cancer. ABSTRACT: Background: Doxorubicin (DOX), used in chemotherapeutic regimens in many cancers, has been known to induce, cardiotoxicity and life-threatening heart failure or acute coronary syndromes in some patients. We determined the role of Substance P (SP), a neuropeptide and its high affinity receptor, NK-1R in chemotherapy associated cardiotoxicity in mice. We determined if NK-1R antagonism will prevent DOX-induced cardiotoxicity in vivo. Methods: C57BL/6 mice (6- week old male) were injected intraperitoneally with DOX (5 mg per kilogram of body weight once a week for 5 weeks) with or without treatment with aprepitant (a NK-1R antagonist, Emend, Merck & Co., Kenilworth, NJ, USA). Five different dosages of aprepitant were administered in the drinking water five days before the first injection of DOX and then continued until the end of the experiment. Each of these 5 doses are as follows; Dose 1 = 0.9 µg/mL, Dose 2 = 1.8 µg/mL, Dose 3 = 3.6 µg/mL, Dose 4 = 7.2 µg/mL, Dose 5 = 14.4 µg/mL. Controls consisted of mice injected with PBS (instead of DOX) with or without aprepitant treatment. The experiment was terminated 5 weeks post-DOX administration and various cardiac functional parameters were determined. Following euthanization, we measured heart weight to body weight ratios and the following in the hearts, of mice treated with and without DOX and aprepitant; (a) levels of SP and NK1R, (b) cardiomyocyte diameter (to determine evidence of cardiomyocyte hypertrophy), (c) Annexin V levels (to determine evidence of cardiac apoptosis), and (d) ratios of reduced glutathione (GSH) to oxidized glutathione (GSSG) (to determine evidence of oxidative stress). Results: We demonstrated that the levels of SP and NK1R were significantly increased respectively by 2.07 fold and 1.86 fold in the hearts of mice treated with versus without DOX. We determined that DOX-induced cardiac dysfunction was significantly attenuated by treatment with aprepitant. Cardiac functional parameters such as fractional shortening (FS), ejection fraction (EF) and stroke volume (SV) were respectively decreased by 27.6%, 21.02% and 21.20% compared to the vehicle treated group (All, p < 0.05, ANOVA). Importantly, compared to treatment with DOX alone, treatment with lower doses of aprepitant in DOX treated mice significantly reduced the effects of DOX on FS, EF and SV to values not significantly different from sham (vehicle treated) mice (All, p < 0.05, ANOVA). The levels of, apoptosis marker (Annexin V), oxidative stress (ratio of GSH with GSSG) and cardiomyocyte hypertrophy were respectively increased by 47.61%, 91.43% and 47.54% in the hearts of mice treated with versus without DOX. Compared to the DOX alone group, treatment with DOX and Dose 1, 2 and 3 of aprepitant significantly decreased the levels of each of these parameters (All p < 0.05, ANOVA). Conclusions: Our studies indicate that the SP/NK1-R system is a key mediator that induces, DOX-induced, cardiac dysfunction, cardiac apoptosis, cardiac oxidative stress and cardiomyocyte hypertrophy. These studies implicate that NK-1R antagonists may serve as a novel therapeutic tool for prevention of chemotherapy induced cardiotoxicity in cancer.